Education Food Security Efforts in West Kalimantan through MSME Education by Bank Kalbar - Didi Haryono; A. Hanief Saha Ghafur; Muhammad Sya’roni Rofi’i (Jurnal Penelitian Pendidikan IPA, 2023)
This research investigates what practical strategies Bank Kalbar can implement to improve family welfare in West Kalimantan through revitalizing education for MSMEs. This research uses a qualitative method with a case study approach. The instrument in this research is interviews. Data was obtained through in-depth interviews with Bank Kalbar and the regional government. Data were analyzed descriptively through stages of data reduction, thematic analysis, and interpretation of findings according to research needs. The research results show that Bank Kalbar has implemented various programs and strategies to strengthen education and socio-economic development to revitalize MSMEs in West Kalimantan. These programs include technical training, digital-based business adaptation, and financing support. Bank Kalbar has also implemented various strategies to strengthen education and socio-economic development, such as internal and external revitalization, network development, and collaboration with various related parties. Provides opportunities to improve family welfare in West Kalimantan, especially for people around MSME locations, such as housewives